Dinamika Studi Islam pada Peguruan Tinggi Keagamaan Islam - Husein Muzakky, Althaf (Universitas Islam Negeri Raden Intan Lampung, 2019)
The Islamic Studies conducted at various Islamic Religious Colleges (PTKI) in Indonesia are proof of the success of the prevailing education system. This paper describes the developments, history, paradigms, problems, urgency, and approaches in Islamic studies in Islamic religious colleges. The dualism paradigm between traditionalists and reformers. The influence of the traditionalist education system that is static is considered frozen in responding to the increasingly dynamic problems of society. A number of modernist figures reformed Islamic studies into a broader scope, critical, methodological, and quality, of course not only in Islamic science that has been developed but equipped with general science and science as a means of scientific change that is more established.